STUDENTS’ PROFILES THROUGH LEARNING APPROACHES USING BIGGS’ STUDY PROCESS QUESTIONNAIRE - Gusti Astika; Toar Y. G. Sumakul (ELTR Journal, 2019)
A number of studies show that students' approaches to learning are important elements to achieve success. Learning approache provides perspectives on the characterisics of good learners. Using R-SPQ-2F (Biggs, Kember, & Leung, 2001), a revised version of Biggs' (1987) Study Process Questionnaire (SPQ), this study attempted to explore the learning approaches of first year students of 2013 academic year at an English Education Program at a private university in Central Java. The purpose of the study was to find out if there was a correlation between the students' approaches to learning and their achievement in an Integrated Course (IC), and describe the profile of their approaches to learning English in the first semester. From 151 respondents participated in this study, it was found that, although weak, there was a positive correlation between students’ achievement scores and their Deep Approach to learning, and a negative correlation between their IC scores and their Surface Approach to learning. This study also found that Deep Motive was associated with the students' achievement. However, the students' profile based on SPQ indicated that the study could not predict the students at risk. Other factors could have affected the students' achievement in their learning.